Rhythmic movement: The role of expectancy and skill in event and emergent timing - Janzen, Thenille Braun (2014)
Recent investigations suggest that rhythmic movements rely on two distinct timing systems: event and emergent timing. Event timing is based on an explicit internal representation of the temporal interval marked by clear perceptual detectible events whereas emergent timing is derived from the dynamics of smooth and continuous movements. However, crucial aspects of the distinction between these mechanisms remain unclear. This thesis investigates the role of expectancy and skill in the internal representation of time in event timing and emergent timing. Chapter 1 introduces the theoretical framework that supports the differentiation between event and emergent timing mechanisms and presents the hypotheses that were tested. Chapter 2 describes a series of five experiments that investigated the role of expectancy through examining the effect of a single unexpected perturbation of feedback content (e.g. pitch, timbre, intensity) on timing of finger tapping. Chapter 3 expands this question by investigating the effect of unexpected auditory perturbations on two types of timed movements: event and emergent timing. The role of expertise and training on motor timing is the subject of discussion of Chapters 4 to 6 where a total of 4 experiments tested the effect of expertise and music training on accuracy of finger tapping and circle drawing tasks. More specifically, Chapter 4 compares accuracy levels of experts in movement-based activities (music and sports) with non experts, whereas Chapters 5 and 6 focus on the effect of music training on event and emergent timing in students of 10 to 14 years of age. Finally, Chapter 7 reviews and discusses the main findings of this body of work with respect to current theories of timing and movement. Foremost, these data challenge current models of human movements controlled by event and emergent timing mechanisms demonstrating that expectancy and training are crucial in determining the timing strategy and the type of expectancy mechanisms adopted to perform distinct rhythmic movements